STRENGTHENING THE PUBLIC HEALTH SYSTEM IN THE TRANSNISTRIAN REGION AND THE REPUBLIC OF MOLDOVA THROUGH THE PRISM OF DIGITISATION - Corina CAUȘAN; Svetlana GOROBIEVSCHI (Eastern European Journal of Regional Studies)
In recent years, the Republic of Moldova has been subject to a series of socio-economic and political challenges. Among the most notable are the Covid-19 pandemic (CoronaVirus 2019), the energy crisis and the political crisis (war in Ukraine). The impact of these crises have radically changed the way of life of the population and influenced the economy, bringing both negative and positive changes. Data were collected from external sources, using qualitative and quantitative method, as well as method of analysis and synthesis, induction, deduction and statistical inference. Comparative analysis was used as a research method in conducting the empirical study. In this article we aim to analyze the positive impact of the Covid-19 pandemic period on the healthcare system, namely: strengthening the public health system through digitalization in the Republic of Moldova and the Transnistrian Moldovan Republic. In order to make a comprehensive analysis of this phenomenon, the indicators that determine the level of development of public health were analysed, namely: the evolution of health expenditure and its share in GDP; life expectancy; medical staff in medical institutions; the degree of sickness and the level of requests for emergency medical assistance. The article presents the digital innovations implemented. Budget execution as an influencing factor was established by analysing the financing of the Semashko and Bismark health systems to expose the degree of flexibility of health service provision in the Republic of Moldova and the Transnistrian region. Thus, following the research, the authors concluded that the consolidation of the public health system through digitization in the Transnistrian region is at an early stage compared to the Republic of Moldova, which is in a stable development. This discrepancy is due to the fact that the Transnistrian region is developing the public health system according to its own scenario and without the involvement of external funding sources. Despite this, digital innovations are developing and are expected to be implemented in the future. Thus, we can observe a much slower development of the implementation of digital innovations to strengthen the health system.